Association of non-insulin-based insulin resistance indices, mean platelet volume and prostate cancer: a cross-sectional study - Jinru Wang; Hengqing An; Ning Tao (BMC Cancer)
Abstract Purpose Insulin resistance and prostate cancer (PCa) association results remain controversial. However, few studies have compared the role of various non-insulin-based insulin resistance (NI-IR) indices and mean platelet volume (MPV) in PCa. Methods We conducted a cross-sectional study, the case group included 354 patients with PCa, and the control group included 1,498 non-PCa participants. We performed inverse probability weighting to reduce the impact of differences in baseline information between the case and control groups on results. Weighted logistic regression analysis for assessing the relationship between NI-IR indices and PCa risk. Fitting 4-point restricted cubic spline (RCS) plots to show the trend of NI-IR indices with PCa risk. The interaction between insulin resistance and platelet volume based on generalized additive model (GAM) to reveal the impact of the interaction between insulin resistance and cardiovascular risk on PCa. In the end, we performed three sensitivity analyses to verify the stability of results. Results Weighted logistic regression analysis revealed that all NI-IR indices were associated with PCa. When NI-IR indices were evaluated as continuous variables, in the all variables adjusted model (model 3), the adjusted OR of ZJU index was 1.337 (95%CI: 1.296–1.379), the adjusted OR of TyG index was 5.300 (95%CI:4.208–6.675), the adjusted OR of TG/HDL-c was 1.431 (95%CI:1.335–1.534), and the adjusted OR of METS-IR was 1.129 (95%CI:1.110–1.149). When NI-IR indices were analyzed as categorical variables, also in model 3, using Q1 as reference, the adjusted OR of ZJU index in Q5 was 15.592 (95%CI:10.809–22.492), the adjusted OR of TyG index in Q5 was 7.306 (95%CI:5.182–10.301), the adjusted OR of TG/HDL-c in Q5 was 4.790 (95%CI:3.459–6.632), and the adjusted OR of METS-IR in Q5 was 9.844 (95%CI:6.862–14.121). RCS displayed that PCa risk tended to increase as the ZJU index, TyG index, TG/HDL-c, and METS-IR increased. The interaction test based on the GAM indicated that the value of the interaction between TG/HDL-c and MPV on the PCa risk was χ2 = 6.924(P = 0.009). With the increase in TG/HDL-c and the decrease in MPV, the PCa risk progressively increases. The sensitivity analysis further confirmed the robustness of the results. Conclusions NI-IR indices were associated with an increased PCa risk. The interaction between MPV and insulin resistance may further contribute to the PCa risk.